TECHNICAL STUDY OF PT XYZ SHIPPING FLOW OF COAL BARGE TO INCREASE DWT (DEADWEIGHT TONNAGE) CAPACITY FROM 5,000 DWT TO 10,000 DWT - Sima, Pasmika (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2022)
Coal is one of the important energy source commodities to carry out industrial activities, which require supporting infrastructure that uses shipping lanes as a means of activity in the delivery of coal from producers to consumers. PT XYZ, in this case as a coal producer, has allocated one of the areas used for coal loading facilities from one of the coal mining located in Gurimbang Village, Sambaliung District, Berau Regency, East Kalimantan Province by using the Berau river channel to the transshipment location in Muara Pantai, Pulau Derawan District, Berau Regency. PT XYZ has obtained a Terminal Permit for Own Interests in the Working Environment and Interest Areas of Tanjung Redeb Port to Support Business Activities in the Coal Mining Sector PT XYZ “TUKS” through the Decree of the Director General of Sea Transportation Number: BX-144/PP 008 concerning Approval Terminal Management for Own Interests in the Work Environment Area and Interest Area of Tanjung Redeb Port to Support Business Activities in the Coal Mining Sector with a capacity of 5,000 DWT. Based on the results of the study of the TUKS flow plan, the position of the general shipping lane, the bathymetry survey of the barge path, the depth of the TUKS pool, the planned loading and unloading volume, the dimensions of the ship that will dock and unload, the frequency of ship visits, the availability of Shipping Navigation Assistance Facilities (SBNP), as well as observations at several points that will become obstacles in shipping navigation, it can be concluded that the development/increase of the DWT TUKS Gurimbang capacity of PT XYZ to support operational activities is still safe enough to be increased to a payload capacity of 8,000 MT with a maximum draft of submerged ships/barges at a depth of -4.70 meters. Therefore, this research can be continued for the preparation of technical review documents as a requirement to fulfill PM 89 of 2018 concerning Norms, Standards, Procedures, and Criteria for Electronically Integrated Business Licensing for the Transportation Sector in the Sea Sector in the process of adjusting DWT (Dead Weight Tonnage) at the Terminal for Self Interest/TUKS PT XYZ in Gurimbang Village.